2012
DOI: 10.1002/ana.23614
|View full text |Cite
|
Sign up to set email alerts
|

Glucocerebrosidase deficiency in substantia nigra of parkinson disease brains

Abstract: ObjectiveMutations in the glucocerebrosidase gene (GBA) represent a significant risk factor for developing Parkinson disease (PD). We investigated the enzymatic activity of glucocerebrosidase (GCase) in PD brains carrying heterozygote GBA mutations (PD+GBA) and sporadic PD brains.MethodsGCase activity was measured using a fluorescent assay in cerebellum, frontal cortex, putamen, amygdala, and substantia nigra of PD+GBA (n = 9–14) and sporadic PD brains (n = 12–14). Protein expression of GCase and other lysosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
546
6
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 493 publications
(601 citation statements)
references
References 39 publications
32
546
6
7
Order By: Relevance
“…Significant reductions in GCase activity were observed in the brainstem, midbrain, cortex, and striatum of SNCA/SNCA mice. This finding further supports existing data, which demonstrate that increased α‐synuclein is associated with decrease in GCase activity in PD brains and in the SH‐SY5Y cell lines overexpressing SNCA 15. Analysis of α‐synuclein protein levels in different brain regions of SNCA/SNCA mice demonstrated approximately 50% increase in α‐synuclein levels compared to wild‐type mice in the brainstem, cortex, and striatum.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Significant reductions in GCase activity were observed in the brainstem, midbrain, cortex, and striatum of SNCA/SNCA mice. This finding further supports existing data, which demonstrate that increased α‐synuclein is associated with decrease in GCase activity in PD brains and in the SH‐SY5Y cell lines overexpressing SNCA 15. Analysis of α‐synuclein protein levels in different brain regions of SNCA/SNCA mice demonstrated approximately 50% increase in α‐synuclein levels compared to wild‐type mice in the brainstem, cortex, and striatum.…”
Section: Discussionsupporting
confidence: 90%
“…It has been shown in SH‐SY5Y cell cultures, neuronal cultures, conduritol‐β‐epoxide (CβE)‐treated mice, and transgenic Gba1 mouse models that reduced GCase activity results in increased α‐synuclein levels 7, 8, 9, 10, 11, 12, 13, 14. Conversely, it has been demonstrated in cell models that increased α‐synuclein causes a decrease in GCase activity 15. Moreover, the biochemical analysis of GBA1 wild‐type Parkinson patients showed that GCase activity and protein levels were significantly reduced in several brain regions,15, 16 further stressing the importance of GCase in PD development.…”
mentioning
confidence: 99%
“…GBA enzyme activity was measured in lysosome-enriched fractions using 4-methylumbelliferyl β-D-glucopyranoside (Sigma, M3633) as a substrate, as in Gegg et al, 2012 [79]. Brain tissue or cell pellets were homogenized in buffer containing 250 mM sucrose, 10 mM Tris, pH 7.4, protease (Roche, 11836170001) and phosphatase inhibitor cocktails (Sigma, P5726).…”
Section: Methodsmentioning
confidence: 99%
“…Another mechanism through which α ‐synuclein accumulation leads to impaired PP2A activity is through the lysosomal enzyme glucocerebrosidase (GCase), which has strong genetic link to PD and is decreased in sporadic PD brains 50, 51. In this regard, accumulation of oligomeric and phosphorylated α ‐synuclein with age in the brains of cynomolgus monkeys is associated with decreased expression and activity of GCase, as well as reduced activity of PP2A particularly in brain regions that are susceptible to α ‐synucleinopathy‐related neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%